Interaction of Hypertension and Insulin Resistance Exacerbates the Occurrence of Diabetes Mellitus in Healthy Individuals - Baomin Wang; Yumei Yang; Xiaomu Li (Journal of Diabetes Research)
Objective. Hypertension and type 2 diabetes are common complications. Patients with hypertension often show insulin resistance. The purpose of this study was to investigate the correlations between different blood pressure levels and different degrees of insulin resistance, as well as their interactions, with newly diagnosed diabetes mellitus. Methods. We conducted a retrospective study on 1251 adult medical examiners who were examined in the Physical Examination Center of Zhongshan Hospital, Fudan University (Shanghai, China) during 2015. All human subjects had no history of diabetes. General clinical data, including blood pressure, fasting glucose and 2-h post-load glucose levels, and lipid profiles, were collected. HOMA-IR was separately calculated. Statistical analyses were carried out by using SPSS software (version 13.0). Results. In 1251 physical examination subjects, a total of 166 cases of newly diagnosed diabetes were detected, with a total detection rate of 13.3%. The rates of newly diagnosed diabetes in the normal blood pressure group, high-normal blood pressure group, and hypertension group were 4.9%, 10.6%, and 19.0%, respectively. Compared with the normal blood pressure group, the proportion of newly diagnosed diabetes in the hypertension group was significantly increased [OR: 2.956, 95% CI 1.736-5.032, P<0.001]. According to the stratification of HOMA-IR level, with the first quartile group (HOMA-IR<1.21) as a reference, the risk of newly diagnosed diabetes in the fourth quartile group (HOMA-IR ≥2.68) was significantly increased. After adjusting for gender and age, for every unit increase in HOMA-IR, the risk of developing newly diagnosed diabetes increased 9.67 times [OR: 9.670, 95% CI 5.086-18.384, P<0.001]. When hypertension was combined with insulin resistance (HOMA-IR ≥2.68), the risk of newly diagnosed diabetes was 38.32 times compared with the control group [OR: 38.315, 95% CI 9.227-159.108, P<0.001]. Conclusions. Elevated blood pressure levels and insulin resistance levels were associated with the risk of newly diagnosed diabetes. Hypertension was an independent risk factor for newly diagnosed diabetes, and the combination of hypertension with insulin resistance further increased the risk of newly diagnosed diabetes.